Melicodenine I, a new quinolinone alkaloid from Melicope denhamii leaves. Issue 8 (18th April 2017) - George, Sony; Venkataraman, Ramaswamy; Baby, Sabulal
Abstract: A new quinolinone alkaloid, Melicodenine I (1 ), along with five known compounds, bergapten (2 ), isoevodionol methyl ether (3 ), isoevodionol (4 ), ternatin (5 ), β-sitosteryl-3-O-β-D-glucopyranoside (6 ) and a mixture of β-sitosterol and stigmasterol were isolated from Melicope denhamii leaves, and their structures were elucidated using 1 H NMR, 13 C NMR, 2D NMR and UPLC-qToF-MS. Abstract :